Effect of infill ratios in SLA 3D printing on mechanical properties of castable wax patterns for molded shells in investment casting. - Thanh Tan Nguyen; Van Tron Tran; Van-Thuc Nguyen; Van Thanh Tien Nguyen (PLoS ONE)
Investment casting has become an integral part of the modern industry's manufacturing process with high precision. However, this technology still faces several challenges that need to be addressed for process improvement, especially the complex and flexible part. This research demonstrates the possibility of applying additive manufacturing techniques (3-dimensional printing (3DP)) and castable wax in investment casting. The main objective is to investigate the effect of infill ratios on the mechanical properties of 3D printed patterns and evaluate the ability to create mold shells using the printed patterns for casting stainless steel SUS 304. The results indicate that the infill density considerably influences the printed samples' mechanical properties, mold-creating ability, weight, and building time. The mechanical properties of the printed samples, including Young's modulus, tensile strength, and work of extension increase from 13.08 MPa, 393.33 MPa, and 4.25 MJ/m3 to 21.72 MPa, 671.48 MPa, and 9.62 MJ/m3, respectively. Moreover, the infill ratios of printed patterns, less than 25%, can be employed to fabricate the IC mold with exceptional quality. The printed patterns' average surface roughness (SR) is 2.49 μm, while the average SR of the casted parts is 7.33 μm. The results strongly strengthen the idea of applying the 3DP technique and castable wax substance in investment casting (IC).